Flora das cangas da Serra dos Carajás, Pará, Brasil: Arecaceae - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2019)
The present study comprises the species of Arecaceae recorded in the canga of the Serra dos Carajás, Pará state, with descriptions, illsutrations and comments regarding the morphology of the species. Five genera and six species were recorded: Attalea maripa, A. spectabilis, Mauritia flexuosa, Mauritiella armata, Oenocarpus distichus and Syagrus cocoides.
Flora of the canga of Serra dos Carajás, Pará, Brazil: Arecaceae
Keywords: Amazônia; FLONA Carajás; Florística; Afloramentos ferruginosos; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA